Synthesis of low-molecular weight itaconic acid polymers as nanoclay dispersants and dispersion stabilizers. (16th January 2023) - Bednarz, Szczepan; Bujok, Sonia; Mielczarek, Kacper; Świergosz, Tomasz; Wierzbicki, Samuel; Konefał, Rafał; Konefał, Magdalena; Nevoralová, Martina; Pavlova, Ewa; Beneš, Hynek
Abstract: Itaconic oligomers with an average molecular weight of Mn  = 1500–2200 g/mol and different end-groups were prepared by 2, 2′-azobis(2-methyl-propionamidine) dihydrochloride (V-50) – induced radical polymerization of itaconic acid (IA) in aqueous solution at 65 °C for 24 h. Mercaptoethanol, thioglycerol, and sodium hypophosphite were used as chain transfer agents (CTA) with the molar ratio ranging from 30:3:1 to 30:3:4 of IA, V50, and CTA, respectively. The structure of the oligomers was confirmed by electrospray ionization mass spectrometry (ESI-MS) and tandem mass spectrometry (ESI-MS/MS). The excellent dispersing efficiency of the oligomers at very low concentrations for Laponite® sols was proved by oscillatory rheology and small-angle X-ray scattering (SAXS) measurements. Graphical abstract: Image 1 Highlights: Itaconic acid oligomers were successfully prepared by radical polymerization. Electrospray ionization mass spectroscopy was used to confirm the chemical structure of the products. The chain-ends type of the oligomers notably affects both dispersing efficiency of Laponite® nanoparticles in water and the dispersions stabilities. The itaconic oligomers show great potential as efficient, bio-based and phosphate-free Laponite® dispersants.